2007
DOI: 10.1152/ajprenal.00098.2007
|View full text |Cite
|
Sign up to set email alerts
|

LGL1, a novel branching morphogen in developing kidney, is induced by retinoic acid

Abstract: Late-gestation lung protein 1 (LGL1) is a glycoprotein secreted by fetal lung mesenchyme that stimulates branching morphogenesis of the developing lung bud. We show that Lgl1 mRNA and protein are also expressed in mesenchymally derived lineages of fetal kidney. Although Lgl1 expression is stimulated by glucocorticoids in kidney cells, cortisol (10(-7) M) actually suppresses ureteric bud branching of fetal kidneys from HoxB7/GFP mice in explant culture. However, early branching morphogenesis in the lung and kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…CRISPLD2 is a molecule recognized in the literature, but no LPSrelated functions are attributed to it (21)(22)(23)(24)(25). We were intrigued by the fact that it contains two LCCL domains, which are characteristic LPS-binding structures (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPLD2 is a molecule recognized in the literature, but no LPSrelated functions are attributed to it (21)(22)(23)(24)(25). We were intrigued by the fact that it contains two LCCL domains, which are characteristic LPS-binding structures (26).…”
Section: Discussionmentioning
confidence: 99%
“…Because it is also known as late gestation lung 1 (Lgl1), it has been implicated in the development of rat lung (21)(22)(23) and mouse kidney (24) and is thought to be involved in the development of nonsyndromic cleft lip with or without cleft palate (25). Its possession of two LCCL domains suggests a relationship to LPS.…”
mentioning
confidence: 99%
“…Upon return to normal oxygen levels, alveolar regeneration was observed, and Capld2 levels returned to normal, suggesting that Capld2 expression was related to septal growth and alveolar partitioning (127). Similarly, within the E12 mouse kidney corresponding to the initiation of branching, retinoic acid-induced expression of Capld2 was observed with a localization to the mesenchyme surrounding the developing kidney (128). At E13.5, CAPLD2 was observed within the mesenchymal cells in the nephrogenic zone and in stromal cells surrounding the ureteric bud trunk.…”
Section: G Crispld2/capld2 Subfamilymentioning
confidence: 92%
“…CRISPLD2/Lgl1 null mice are embryonic lethal by embryonic day 9.5 [60]. CRISPLD2/Lgl1 heterozygous knockout mice appear grossly normal, but lung maturation is delayed and ureteric bud branching is reduced at the fetal stage [60,61]. Chiquet et al [62] reported an association between the CRISPLD2 gene and nonsyndromic cleft lip with or without cleft palate.…”
Section: Discussionmentioning
confidence: 99%